International Students Dictionary - Johnson, Karen; Wells, Lisa (Journal of International Students, 2016)
According to Study Destination USA’s website, The Ultimate International Student Dictionary for International Students Studying in the USA was created to give transferring international students help with the unique terminology used in universities and colleges in the United States. From experience, the staff at Study Destination USA understands the challenges future or current international students will experience, such as adapting to a new academic culture to understanding the nuances of the university language.